2005
DOI: 10.1016/j.orthres.2004.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low intensity pulsed ultrasound and BMP-2 on rat bone marrow stromal cell gene expression

Abstract: To determine how low intensity pulsed ultrasound alters gene expression in rat bone marrow stromal cells and to see if combining this stimulation with BMP-2, cells were pre-cultured for eight days in the presence of 50 &ml ascorbic acid and then exposed to either low intensity US or 100ng/ml BMP-2 or both combined, beginning on the first, third fifth or seventh day of culture so that cells were exposed to the stimuli for one, three, five or seven days. Real time PCR was used to determine the effect of these tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
50
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 18 publications
1
50
0
1
Order By: Relevance
“…On the other hand, an electromagnetic field and ultrasound are nonbiomimetic stimuli frequently used for treatment of bone fracture. Even though these stimuli are effective for enhancing osteogenic differentiation and bone formation, [12][13][14][15][16] there are still only a few articles reporting the effects of combining two or more stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, an electromagnetic field and ultrasound are nonbiomimetic stimuli frequently used for treatment of bone fracture. Even though these stimuli are effective for enhancing osteogenic differentiation and bone formation, [12][13][14][15][16] there are still only a few articles reporting the effects of combining two or more stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…The recent use of morphogenetic proteins, growth factors and low-intensity ultrasound compose the scientific effort for this purpose. 2,6,9,25,27,29 Studies seek to elucidate the response of soft tissues to the gradual movement of the bone in which they are inserted. Some of these changes seem more favorable when using the distraction technique than when using the conventional orthognathic surgery, like the improvement of lips and nose, as consequence of the maxillary advancement.…”
mentioning
confidence: 99%
“…It was reported that LIPUS irradiation increases the levels of aggrecan mRNA in cartilage cells in vitro and in vivo 10,13) and prostaglandin E2 (PGE 2 ) by induction of Cox-2 in mouse osteoblastic cell line 14) . LIPUS irradiation of rat bone marrow stromal cells induces the expression of Cbfa1 at an early stage 15) . An increase in Cox-2 and osteopontin (OPN) mRNA was detected in rat bone marrow-derived stromal cells 3 h after LIPUS irradiation 16) .…”
Section: Discussionmentioning
confidence: 99%